Analisis Sistem Informasi Akuntansi Penjualan dan Pengendalian Internal pada PT Dwi Ola - Tsyaniah; Andrian Noviardy (Masyarakat Ekonomi Syariah Bogor, 2025)
The sales accounting information system and internal control are crucial components in ensuring the operational effectiveness and accuracy of financial statements in the company. This study focuses on PT Dwi Ola, which relies on LPG gas sales, to analyze the implementation of cash and credit sales accounting information systems as well as existing internal controls. The results of the study show that although the accounting information system at PT Dwi Ola already includes transaction recording and sales reports, there are still weaknesses in system integration that result in inconsistencies between physical stock and system records. In addition, internal controls are not optimal, with a lack of separation of duties and a robust authorization system, potentially increasing the risk of fraud. This study recommends the importance of separation of functions, improvement of internal control systems, and increased supervision to improve efficiency and accuracy in the sales process and recording of transactions in the company.